Potensi dan Proses Pemberdayaan Petani Garam di Desa Kusamba Kecamatan Dawan Kabupaten Klungkung - I PUTU BAGUS YOGANA; I GEDE SETIAWAN ADI PUTRA; NYOMAN PARINING (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2016)
Potential and Empowerment Process Salt Farmers in Kusamba Village Dawan District Klungkung RegencyKusamba Village, Dawan District, Klungkung Regency has large salt potential. Butstill faces obstacles as: (i) cheaper salt price outside Bali Province; (ii) weatherfactor that hinders production; and (iii) low management marketing. The purpose ofresearch to know : (1) the characteristic of salt farmers; (2) the salt businesspotential; and (3) salt farmer’s aspects and empowerment elements. This researchuses the qualitative and quantitative analysis method. The research results show :(1) the salt farmers’s age classified as productive, formal education level classifiedas low, farming experience is considered relatively versed, and their land were verysuitable for expanded; (2) viewed from the potential perspective, the salt color iscolorless white, the sense is not bitter, interesting packaging, higenis, having exportopportunity, and able to compete in the market; (3) asset ownership classified asgood, the relationship between individuals and groups classified as good, most ofsalt farmers want the institutional strengthening, partnership synergies was stillunder local partnership, the chance to expand their salt’s businesses classified asgood, physical participation in an effort to salt business development have gooddiscipline, salt farmers having a sense of good responsibility to their job and theirfamilies, and the ability to cooperate and organizing classified as good.